New Keynesian macroeconomics: Entry for New Palgrave Dictionary of Economics, 2nd Edition - Huw David Dixon (Cardiff University, Cardiff Business School, 2007)
This dictionary entry defines the development of new Keynesian macroeconomics (NKM) since the 1980s. I argue that the key defining feature NKM is the introduction of imperfect competition, making price and/or wage setting endogenous and hence allowing for a rigorous understanding of nominal rigidity. This has led to a shift away from perfect competition in macroeconomics. The combination of NKM with dynamic macroeconomic modelling has led to the current orthodoxy: the new-neoclassical synthesis. Dynamic wage and price models lead to monetary neutrality in steady-state, non-neutrality out of steady-state. Other themes in NKM include efficiency wage theory and coordination failure.
Keywords: E1; E3; E4; B22; 330; Keynesian; nominal; rigidity; new; Neukeynesianische Makroökonomik; Preisrigidität; Lohnrigidität; Mikroökonomische Fundierung; Theorie